The Effect of Person-Organization Fit on Turnover Intention with Job Satisfaction as Mediating Variable - Khalida, Rahmi; safitri, Nurul (UI Scholars Hub, 2018)
Currently, the sharia banking industry continues to grow and develop. Furthermore, one of the fastest growing sharia banks is Sharia Mandiri Bank (BSM). Every company including sharia banking faces the challenge of attracting, developing, and retaining its employees. This study aims to examine the effect of person-organization-fit (P-O fit) on employee turnover intention in Sharia Mandiri Bank (BSM) by considering job satisfaction as a mediating variable. Multidimensional P-O fit, namely supplementary fit, complementary fit, needs-supplies fit and demands-abilities fit (Piasentin, 2007), Michigan Organizational Assessment Questionnaire (Camman et al. 1979) and Mobley, Horner and Hollingsworth’s (1978) revised model were used to measure P-O fit, job satisfaction and turnover intention. A quantitative survey was conducted on a non-probability (purposive) sample of 100 permanent employees working at PT Bank Syariah Mandiri. Correlation, multistage regression and bootstrap were used to test the direct and mediating relationship between key variables. The results uncovered that there is a moderate negative correlation between P-O fit and turnover intention, a strong positive correlation between P-O fit and job satisfaction, and a moderate negative correlation between job satisfaction and turnover intention. The simple regression analysis showed that P-O fit is a significant predictor of job satisfaction and both P-O fit and job satisfaction were significant predictors to turnover intention. Bootstrapping test revealed a statistical support for the indirect effect of P-O fit on turnover intention through job satisfaction. Moreover, the results of multistage regression analysis confirm that job satisfaction significantly mediated the relationship between P-O fit and turnover intention as a full mediator. The results and implications of the study are discussed and recommendations for future research are addressed.